2012
DOI: 10.1021/om3010838
|View full text |Cite
|
Sign up to set email alerts
|

Anionic Nickel(II) Complexes with Doubly Deprotonated PNP Pincer-Type Ligands and Their Reactivity toward CO2

Abstract: The aromatization−dearomatization reaction of pincer-type complexes prompted by protonation−deprotonation of the pincer "arm" is a key step in bond activation chemistry and atom-economic catalytic transformations. However, the possibility of double deprotonation of ancillary pincer ligands is rarely discussed in the literature. Here we report on square-planar cationic nickel(II) complexes of PNP R type ligands (PNP = 2,6-bis[(dialkylphosphino)methyl]-pyridine with R = i Pr, t Bu), which can be readily transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
62
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 72 publications
8
62
0
Order By: Relevance
“…3 In line with the latter, we have recently observed that ammonia–borane dehydrogenation catalysts 1 and 2 (Figure 1A), 4 each bearing an anionic bidentate borate ligand, are capable of CO 2 reduction concurrent with ammonia–borane dehydrogenation. We therefore became interested in investigating the reactivity of other nickel complexes of the anionic bidentate ligand dimethylbis(2-pyridyl)borate ( 3 ; Figure 1B).…”
Section: Introductionsupporting
confidence: 63%
“…3 In line with the latter, we have recently observed that ammonia–borane dehydrogenation catalysts 1 and 2 (Figure 1A), 4 each bearing an anionic bidentate borate ligand, are capable of CO 2 reduction concurrent with ammonia–borane dehydrogenation. We therefore became interested in investigating the reactivity of other nickel complexes of the anionic bidentate ligand dimethylbis(2-pyridyl)borate ( 3 ; Figure 1B).…”
Section: Introductionsupporting
confidence: 63%
“…In particular, coordinated phosphines should be compared to phosphonium substituents (P V ), that is, highly stabilizing towards the conjugate base carbanion, with considerable precedent. Both benzylic arms have been singly deprotonated in a PNP pincer complex of Ni II , whereby the buildup of negative charge on the dianionic ligand was determined, yet the electrophile CO 2 attacked the benzylic carbon atom, with no bond formation between CO 2 and nickel . The singly benzyl deprotonated product failed to react with CO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…In this way the scope of pincer complex chemistry has been expanded. This has been demonstrated in a number of stoichiometric reactions 13,14 and catalytic transformations. 15,16 In these cases the metal ligand cooperation acts via dearomatisation and aromatisation steps of the ligand backbone, 17 which is facilitated by the acidic protons of the ring methylene groups and the ability of nitrogen to offer different binding modes to the metal centre.…”
Section: Introductionmentioning
confidence: 90%